Simplify g^2-20gh-g+20h.

2 Answers | Add Yours

justaguide's profile pic

justaguide | College Teacher | (Level 2) Distinguished Educator

Posted on

If by simplify you mean factorize, we have to factorize: g^2 - 20gh - g + 20h

g^2 - 20gh - g + 20h

factorize the the common factor (g - 20h)

=> g(g - 20h) - 1(g - 20h)

=> (g - 1)(g - 20h)

The factorized form is g^2 - 20gh - g + 20h = (g - 1)(g - 20h).

giorgiana1976's profile pic

giorgiana1976 | College Teacher | (Level 3) Valedictorian

Posted on

The first step is to create groups of terms:

g^2-20gh-g+20h = (g^2-20gh)-(g-20h)

We'll factorize by g the first group:

g^2-20gh-g+20h = g(g - 20h) - (g - 20h)

We'll factorize by (g - 20h):

g^2-20gh-g+20h =  (g - 20h)(g - 1)

The simplified expresison is: g^2-20gh-g+20h = (g - 20h)(g - 1)

We’ve answered 318,911 questions. We can answer yours, too.

Ask a question